The Role of New Media in the Modern Marketing Strategy of TelecommunicationsCompanies: Asiacell and Korek Telecom as Case Studies. (Raparin Journal of Humanities (RJH), 2025)
This research, titled "The Role of New Media in the Modern Marketing Strategy of Telecommunications Companies (Asiacell and Korek Telecom as Case Studies)", is a descriptive study, employing a suitable research method to obtain accurate and detailed data. A field method was used for data collection. The research community consists of Asiacell and Korek Telecom companies. The sample includes 102 employees from the marketing departments of both companies, selected through purposive sampling. The researcher relied on a structured questionnaire as the primary tool for data collection.The main objectives of the research are:• To identify the significance of new media in the marketing strategies of Korek Telecom and Asiacell.• To assess the extent to which modern marketing objectives are achieved by both companies.• To evaluate the effectiveness of Korek Telecom and Asiacell in utilizing the features of modern marketing through new media.Key findings of the study include:• New media holds great importance in the modern marketing strategies of telecommunications companies. Both companies assign high value to the use of new media platforms in promoting their services to customers.• The telecommunications companies place strong emphasis on market research and identifying customer needs, which facilitates better service delivery during various stages of modern marketing.• The telecommunications companies aim to offer the most comprehensive services with continuity and consistency.• Modern marketing strategies assist these companies in promoting their products and services, and in identifying challenges in delivering their services.